2015
DOI: 10.1088/1475-7516/2015/08/051
|View full text |Cite
|
Sign up to set email alerts
|

Quantisation of the holographic Ricci dark energy model

Abstract: While general relativity is an extremely robust theory to describe the gravitational interaction in our Universe, it is expected to fail close to singularities like the cosmological ones. On the other hand, it is well known that some dark energy models might induce future singularities; this can be the case for example within the setup of the Holographic Ricci Dark Energy model (HRDE). On this work, we perform a cosmological quantisation of the HRDE model and obtain under which conditions a cosmic doomsday can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
(149 reference statements)
0
14
0
Order By: Relevance
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…However, as energy density diverges in all the cases presented, one might expect that quantum effects become important at some point in the future evolution. In fact, a quantum analysis shows that in all cases, the classical abrupt event can be avoided from a quantum point of view [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For a FLRW universe, this singularity is usually present in a universe which is spatially closed and filled with matter satisfying the strong energy conditions (but see [54] for a counterexample). Type I A big rip singularity takes place at finite cosmic time with infinite scale factor, where the Hubble parameter and its cosmic time derivative diverge [55,56,37,30,57,58,59,60,2,61]. The occurrence of this singularity is intrinsic to phantom dark energy.…”
Section: Cosmic Curvature Singularities (At a Finite Time): Gr And Bementioning
confidence: 99%